Analisis Strategi Pengembangan Unit Pelaksana Teknis Pengembangan Benih Holtikultura di Lingkungan Dinas Pertanian Provinsi Jawa Timur - Syafi'i, Ahmad (Journal of Community Service and Society Empowerment, 2024)
This research aims to carry out a strategic analysis of the development of the Seed Development Technical Implementation Unit within the East Java Province Agricultural Service. The results of the SWOT Analysis and General Electric (GE) analysis show that the Technical Implementation Unit for Horticultural Seed Development (UPT PB Horticulture) has strengths and challenges in industrial competition. Horizontal and vertically integrated development strategies are need to overcome competitive challenges and utilize existing strengths. Internal and external integration, together with intensive and diversification strategies, will strengthen UPT PB Horticulture's position in the horticulture industry, increase competitiveness, and achieve sustainable growth. Strategic suggestions include focusing on product varieties that are in demand in the market, revitalizing production infrastructure, developing processed products through partnerships, appropriate production scheduling, improving HR management, increasing access to capital, partnerships for market development, investing in modern production infrastructure, and improving marketing. , promotion, and distribution. Appropriate production scheduling strategies and market analysis are need to overcome the obstacles faced.